Sweden : 2003 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2003)
The Swedish economy recovered from the crisis, assisted by a sizable fiscal stimulus. Executive Directors commended the fiscal and monetary frameworks, skillful and proactive management of monetary policy of the Riksbank, the soundness of the financial system, and stressed the need to accelerate structural reforms. They welcomed the steps to strengthen the financial system, according to the Financial Sector Assessment Program recommendations. They appreciated the authorities for exemplary efforts to promote open trade policies, and for the high level of official development assistance.